Answer:
0
Step-by-step explanation:
32=32+0
Answer: This problem is all mixed up. There is no way to solve it with it like this.
Step-by-step explanation:
x is the 1st number, y is the 2nd number, z is the 3d number.
x+y+z = 2
x - y + z= -2
x - z = y +22 -----> x-y-z=22
x+y+z = 2
<u>x - y + z= -2</u>
2x + 2z =0
x + z = 0
x = -z
x - y + z= -2 and x = -z
-z - y + z = -2, y =2
x-y-z=22 and x = -z, and y = 2 -----> x -2 +x = 22 --->2x = 24 ----> x = 12
x= -z -----> z = - 12
Answer: what's the results of the stimulation?, there's not much info to answer your question.
Step-by-step explanation:
Answer:
(2, -5)
Step-by-step explanation:
Convert to vertex form:
3x^2 - 12x + 7
= 3(x^2 - 4x) + 7
Completing the square:
= 3[ (x - 2)^2 - 4)] + 7
= 3(x - 2)^2 - 12 + 7
= 3(x - 2)^2 - 5.
Comparing with the general form
a(x - b)^2 + c we see that the vertex is (b, c) = (2, -5).